THE IMPLEMENTATION OF THINK PAIRS WRITE TECHNIQUE TO IMPROVE THE STUDENTS WRITING DESCRIPTIVE TEXT (Classroom Action Research To the second year students of MTsN Bireuen) - Misnar, Misnar (Jurnal Pendidikan Almuslim, 2017)
This article aimed to know implementing of Think Pairs Write Techniqe Improve the Students Writing Descriptive Text to the second year students of MTsN Bireuen). From the title above, the researcher formulated the problem of this research are (1) How does Think Pairs Write Technique improve the students writing descriptive text at the second year students of MTsN Bireuen. The researchwas done because the researcher found that most of the second year students of MTsN Bireuen especially in class VIII3 can not write english well, most of them have difficulty in finding the ideas in writing and they were not responsive in learning writing because the technique or writing that used by the teacher at that school were not effective and interactive. The research subject was the second year students of MTsN Bireuen of class VIII3. This class consisted of 28 students, the instruments of this research were test, observation sheet, quetionnaires, and field notes. The design of this research was classroom action research that was done in two cycles. The result of test in the first cycle was 65,8. While in the second cycle total score was 77,7. The students were reached the criteria of success after being model of Think Pairs Write Technique. It was mean that TPW technique improve the students in writing descriptive text.